Longitudinal data on speech outcomes in internationally adopted children compared with non‐adopted children with cleft lip and palate - Okhiria, Åsa; Persson, Christina; Johansson, Monica Blom; Hakelius, Malin; Nowinski, Daniel (International journal of language & communication disorders, 2023)
Background At the beginning of the 21st century, international adoptions of children with cleft lip and/or palate increased dramatically in Sweden. Many children arrived partially or totally unoperated, despite being at an age when palatoplasty has usually been performed. To date, the speech development of internationally adopted (IA) children has been described up to age 7–8 years, but later development remains unstudied. Aims To investigate speech development between ages 5 and 10 years in children born with cleft lip and palate (CLP) adopted from China and to compare them with non‐adopted (NA) children with CLP. A secondary aim was to compare the frequencies of secondary palatal surgery and number of visits to a speech and language pathologist (SLP) between the groups. Methods & Procedures In a longitudinal study, 23 IA children from China were included and matched with 23 NA children born in Sweden. Experienced SLPs blindly reassessed audio recordings from routine follow‐ups at ages 5 and 10 years. Velopharyngeal function (VPF) was assessed with the composite score for velopharyngeal competence (VPC‐Sum) for single words and rated on a three‐point scale (VPC‐Rate) in sentence repetition. Target sounds in words and sentences were phonetically transcribed. Per cent correct consonants (PCC) were calculated at word and sentence levels. For in‐depth analyses, articulation errors were divided into cleft speech characteristics (CSCs), developmental speech characteristics (DSCs) and s‐errors. Information on secondary palatal surgery and number of visits to an SLP was collected. Outcomes & Results VPF differed significantly between the groups at both ages when assessed with VPC‐Sum, but not with VPC‐Rate. Regardless of the method for assessing VPF, a similar proportion in both groups had incompetent VPF but fewer IA than NA children had competent VPF at both ages. IA children had lower PCC at both ages at both word and sentence levels. More IA children had CSCs, DSCs and s‐errors at age 5 years, and CSCs and s‐errors at age 10. The development of PCC was significant in both groups between ages 5 and 10 years. The proportion of children receiving secondary palatal surgery did not differ significantly between the groups, nor did number of SLP visits. Conclusions & Implications CSCs were more persistent in IA children than in NA children at age 10 years. Interventions should target both cleft and DSCs, be comprehensive and continue past the pre‐school years. WHAT THIS PAPER ADDS What is already known on this subject At the beginning of the 21st century, IA children with cleft lip and/or palate arrived in Sweden partially or totally unoperated, despite being at an age when palatoplasty has usually been performed. Studies up to age 7–8 years show that adopted children, compared with NA peers, have poorer articulation skills, demonstrate both cleft‐related and developmental articulation errors, and are more likely to have velopharyngeal incompetence. Several studies also report that adopted children more often require secondary palatal surgery due to fistulas, dehiscence or velopharyngeal incompetence compared with NA peers. What this paper adds to existing knowledge This longitudinal study provides additional knowledge based on longer follow‐ups than previous studies. It shows that the proportion of children assessed to have incompetent VPF was similar among IA and NA children. It was no significant difference between the groups regarding the proportion that received secondary palatal surgery. However, fewer IA children were assessed to have a competent VPF. Developmental articulation errors have ceased in most IA and all NA children at age 10 years, but significantly more adopted children than NA children still have cleft‐related articulation errors. What are the potential or actual clinical implications of this work? Speech and language therapy should target both cleft‐related and developmental articulation errors. When needed, treatment must be initiated early, comprehensive, and continued past the pre‐school years, not least for adopted children.